Decellularization and engineered crosslinking: a promising dual approach towards bioprosthetic heart valve longevity. (7th September 2020) - Human, Paul; Ofoegbu, Chima; Ilsley, Helen; Bezuidenhout, Deon; de Villiers, Jandre; Williams, David F; Zilla, Peter
Abstract: OBJECTIVES: While decellularization has previously significantly improved the durability of bioprosthetic tissue, remnant immunogenicity may yet necessitate masking through crosslinking. To alleviate the fears of reintroducing the risk of calcific degeneration, we investigated the application of rationally designed crosslinking chemistry, capable of abrogating mineralization in isolation, in decellularized tissue. METHODS: Bovine and porcine pericardium were decellularized using the standard Triton X/sodium deoxycholate/DNAse/RNAse methodology and thereafter combined incrementally with components of a four-stage high-density dialdehyde-based fixation regimen. Mechanical properties prior to, and calcium levels following, subcutaneous implantation for 6 and 10 weeks in rats were assessed. RESULTS: Enhanced four-stage crosslinking, independent of decellularization, or decellularization followed by any of the crosslinking regimens, achieved sustained, near-elimination of tissue calcification. Decellularization additionally resulted in significantly lower tissue stiffness and higher fatigue resistance in all groups compared to their non-decellularized counterparts. CONCLUSIONS: The dual approach of combining decellularization with enhanced crosslinking chemistry in xenogeneic pericardial tissue offers much promise in extending bioprosthetic heart valve longevity. Abstract : Bioprosthetic heart valves have 2 major advantages over mechanical valves: they do not require anticoagulation and they can be crimped for transcatheter deployment.